WORD CHANGE IN WORDPLAY BY TEENANGERS ON TWITTER: A SOCIOLINGUISTIC STUDY (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
AbstractThere are always a new slang language that teenagers use from period to period. New slang language that teenagers use are word change. Word change is usually used by teenangers because of following the previous speaker and make it as a habit language for them. Word change in wordplay patterns on Twitter will be researched that written by teenagers. The main object of this reserach is Twitter. The purpose of this research is to analyze word change in wordplay patterns by teenangers written on Twitter. Qualitative method is used in this research. Documentary study is used and the data written desciprtively. The subject of this research are the teenagers between 13-22 years old who write documentation on Twitter using word change in wordplay as the main data. Basic and advanced technique are used in describing the data. The result of this research shown that there are 8 wordplay patterns with word change revealed in 8 data written by teenagers using wordplay in Twitter.Keywords: slang language, teenagers language, wordplay, word change, twitter